Analisis Faktor-Faktor Perambahan Hutan pada Kawasan Resort Konservasi Wilayah II Taman Wisata Alam (TWA) Ruteng di Desa Ngkiong Dora Kecamatan Lamba Leda Timur, Kabupaten Manggarai Timur, Provinsi Nusa Tenggara Timur - Berta Adelina Ria; Ludji Michael Riwu Kaho; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
This study aims to determine the factors that cause forest encroachment in TWA Rutengside Ngkiong Dora Village.The research method used is descriptive qualitative analysis and percentage tabulation.sampling technique used purposive sampling. The data collection was done through structured interviews, in-depth interviews, field observations, documentation and literature studies. The results of the study concluded that forest destruction in TWA Rutengside Ngkiong Dora Village was caused by 3 (three) factors, namely; economic factors, community socio-cultural factors, and the limited number of forest security supervisors.Economic factors refer to the area of land owned by the community which is categorized as